2022
DOI: 10.1136/openhrt-2021-001942
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiotropic viruses in adults with clinically suspected myocarditis in South Africa

Abstract: ObjectivesTo determine the prevalence and types of viral pathogens in the myocardium of patients presenting with clinically suspected myocarditis in South Africa.MethodThis is a prospective cross-sectional study. Consecutive adults presenting to a single tertiary centre in South Africa between August 2017 and January 2021 who fulfilled the European Society of Cardiology’s diagnostic criteria for clinically suspected myocarditis and who had undergone the appropriate investigations, including cardiac MRI (CMR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…Gradually, this pattern shifted predominantly toward parvovirus B19 and HHV-6 infection [ 29 , 30 ]. However, this is still highly variable and particularly varies according to the geographic location and temporal differences, as other recent studies still showed a higher prevalence of enteroviruses, particularly, Coxsackievirus in some regions [ 5 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gradually, this pattern shifted predominantly toward parvovirus B19 and HHV-6 infection [ 29 , 30 ]. However, this is still highly variable and particularly varies according to the geographic location and temporal differences, as other recent studies still showed a higher prevalence of enteroviruses, particularly, Coxsackievirus in some regions [ 5 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of specific cardiotropic viruses is variable over time, Parvovirus B19 (PVB19) and human herpes virus-6 (HHV6) have been increasingly detected in EMB of patients with acute myocarditis over the past 20 years [ 16 ]. A recent report from South Africa showed an almost similar distribution [ 16 ]. It is not clear yet if this is the case in Egypt or not.…”
Section: Introductionmentioning
confidence: 99%
“…Although coxsackieviruses were the viruses that were most commonly associated with myocarditis in the 20th century, a shift in detected cardiotropic viruses has been observed in recent decades, concurrent with the switch from traditional serology-based methods to the more sensitive nucleic acid tests such as in situ hybridization, and later polymerase chain reaction (PCR) [73,74]. Several studies have reported an increased incidence of parvovirus B19 and herpes viruses, such as human herpes virus 6, in endomyocardial biopsies [75][76][77]. Furthermore, new data show that active viral transcriptional activity plays a determining role in patient outcome, thereby necessitating looking beyond the mere detection of inflammation and viral genomes to evaluate the prognosis as the basis of establishing the best course of treatment for patients [78].…”
Section: Virus Diagnosticsmentioning
confidence: 99%
“…Like EVs, the dsDNA adenoviruses (AdV) were considered a major cause of nonischemic heart disease alongside EVs as reported by EMBs or autopsy-based studies in the 1990s and early 2000s [124][125][126]. However, detection of other cardiotropic viruses began to be more frequent thereafter, with recent studies suggesting that both EVs and AdV no longer play a dominant role in viral myocarditis [75][76][77]127,128]. Whether this shift truly reflects an epidemiological change or merely a trend of better detection of previously underreported viral infections has yet to be determined.…”
Section: Enteroviruses and Adenovirusesmentioning
confidence: 99%
“…Endomyocardial biopsy has shown an evident shift in the prevalence of cardiotropic viruses over time 29 , 32 . Provided the broad repertoire of causative viral pathogens, the possibility of the Mpox virus as another emerging cardiotropic virus cannot be ruled out.…”
Section: Pathophysiologymentioning
confidence: 99%